1979
DOI: 10.1002/bjs.1800660206
|View full text |Cite
|
Sign up to set email alerts
|

The reproducibility of the station pullthrough technique for measuring lower oesophageal sphincter pressure

Abstract: The results are presented of two studies of the station pullthrough technique for lower oesophageal manometry. The first part of the work is an assessment of the reproducibility of this technique using both an infused tube system and a system of subminiature, intraluminal strain gauge transducers. The second part of this report describes a study into the effect that the position of the recording hole on the probe may have in relation to the measured pressure for the lower oesophageal sphincter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

1980
1980
1992
1992

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Although reservations about the reproducibility of this technique have been voiced (Perez-Avila and Irvin, 1975), we have recently confirmed that the reproducibility of the SPT is satisfactory (Hay et al, 1979). The SPT does, however, require cumbersome plumbing and the interpretation of the resultant recordings is frequently difficult because of the superimposition of respiratory and swallow waves.…”
supporting
confidence: 57%
See 3 more Smart Citations
“…Although reservations about the reproducibility of this technique have been voiced (Perez-Avila and Irvin, 1975), we have recently confirmed that the reproducibility of the SPT is satisfactory (Hay et al, 1979). The SPT does, however, require cumbersome plumbing and the interpretation of the resultant recordings is frequently difficult because of the superimposition of respiratory and swallow waves.…”
supporting
confidence: 57%
“…We have shown that the SPT technique, if performed with care and attention to detail, can give results which are reproducible both from hour to hour and day to day (Hay et al 1979). …”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations